Pengaruh Status Sosial Ekonomi Orang Tua Dan Motivasi Belajar Terhadap Minat Melanjutkan Studi Ke Perguruan Tinggi Siswa Kelas XII Program Keahlian Otomatisasi Tata Kelola Perkantoran SMK Negeri 3 Surakarta Tahun Ajaran 2023/2024 - Novita Dwi Maharani; Dyah Sulistyaningrum; Susantiningrum Susantiningrum (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study employs a quantitative descriptive method. The research population is the 2023/2024 academic year students of SMK N 3 Surakarta, totaling 450 students. The sampling technique used is random sampling with 45 students as the sample. The data collection method utilizes questionnaires. Data analysis is conducted using multiple linear regression and analysis prerequisites, including normality, linearity, and multicollinearity tests. The research findings are as follows: A significant influence of parents' socioeconomic status on the interest in continuing studies to higher education was found. A significant influence of learning motivation on the interest in continuing studies to higher education was found. A positive and significant combined influence of parents' socioeconomic status and learning motivation on the interest in continuing studies to higher education was established. This was supported by the finding that F counting (calculated F-value) = 11.891 > F tabel (tabled F-value) = 3.32, leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). This result indicates that the higher the parents' socioeconomic status and learning motivation simultaneously, the higher the interest of SMK N 3 Surakarta students in continuing their studies to higher education.